2004
DOI: 10.1254/jphs.95.56
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine Protects Against Intracranial Hypertension and Cerebral Ischemic Injury in Experimental Heatstroke

Abstract: Abstract. The aim of the present study was to ascertain whether aminoguanidine attenuated intracranial hypertension and cerebral ischemic injury in experimental heatstroke. Urethaneanesthetized rats were exposed to heat stress (ambient temperature of 43°C) to induce heatstroke. Control rats were exposed to 24°C. Mean arterial pressure, cerebral perfusion pressure, and cerebral blood flow after the onset of heatstroke were all significantly lower than in control rats. However, colonic temperature, intracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
8
31
0
Order By: Relevance
“…Indeed, both present and previous (26,27) results have shown that both cerebral ischemia and injury that occurred during heatstroke are associated with an increased production of glycerol, lactate / pyruvate ratio, and glutamate in the brain. Our results further demonstrated that PO 2 in the rat brain was greatly reduced after the onset of heatstroke.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, both present and previous (26,27) results have shown that both cerebral ischemia and injury that occurred during heatstroke are associated with an increased production of glycerol, lactate / pyruvate ratio, and glutamate in the brain. Our results further demonstrated that PO 2 in the rat brain was greatly reduced after the onset of heatstroke.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, the NO overproduction could be observed (ref. 5 and the present results) and iNOS inhibitors (30) …”
Section: Stress Accordingly Cd34supporting
confidence: 72%
“…Indeed, plasma or cerebral levels of NO are elevated in heatstroke rats (27,28; present results). Aminoguanidine, an inducible nitric oxide synthase (iNOS) inhibitor, improves heat tolerance in the rat by preserving the splanchnic blood flow (29) and reducing intracranial hypertension and cerebral ischemia and damage (30). An early exposure to HUCBC (5), in addition to ameliorating iNOS-dependent NO overproduction in brain, causes attenuation of cerebrovascular dysfunction or injury that occurred during heatstroke in the rat.…”
Section: Stress Accordingly Cd34mentioning
confidence: 99%
“…Both pyrogenic cytokines can interfere with normal thermoregulation, thereby precipitating arterial hypotension, hyperthermia, and heatstroke (1). Recent reports have also shown that aminoguanide, an iNOS inhibitor, slows the rate of NO production, preserves the splanchnic (8) and cerebral blood flow (10), and improves heat tolerance in rats. However, relative little evidence is available about the effects of iNOS inhibition on the renal ischemia and damage during heatstroke.…”
Section: Introductionmentioning
confidence: 99%
“…This alteration allows leakage of endotoxins and increases production of inflammatory cytokines that induce release of NO and endothelins (10,11). Both pyrogenic cytokines can interfere with normal thermoregulation, thereby precipitating arterial hypotension, hyperthermia, and heatstroke (1).…”
Section: Introductionmentioning
confidence: 99%